Peace negotiation in the Cordillera region - Arciso, Theodore E. (Baguio City : Baguio Central University, 1987)
The present study is a narrative assessing the peace negotiation in the Cordillera region which was participated by three major groups namely: the Cordillera Bodong Aministration (CBA), the Cordillera Broad Coalition (CBC), the government panel which included the local government units (LGU).
In partial fulfillment of the requirements for the Degree Masters in Public Administration
A thesis presented to the Faculty of the Graduate School, Baguio Central University
Thesis (M.P.A)-Baguio Central University
Keywords: Peace; Reconciliation